2010
DOI: 10.1038/emboj.2010.137
|View full text |Cite
|
Sign up to set email alerts
|

NANOG regulates glioma stem cells and is essential in vivo acting in a cross-functional network with GLI1 and p53

Abstract: A cohort of genes associated with embryonic stem (ES) cell behaviour, including NANOG, are expressed in a number of human cancers. They form an ES-like signature we first described in glioblastoma multiforme (GBM), a highly invasive and incurable brain tumour. We have also shown that HEDGEHOG-GLI (HH-GLI) signalling is required for GBM growth, stem cell expansion and the expression of this (ES)-like stemness signature. Here, we address the function of NANOG in human GBMs and its relationship with HH-GLI activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
320
1
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(350 citation statements)
references
References 64 publications
(150 reference statements)
17
320
1
5
Order By: Relevance
“…In this tumor type, Nanog, a homeoprotein required to maintain ES pluripotency [66], appears essential for SC functions as its inactivation reduces neurosphere formation in vitro and GBM growth in vivo. Importantly, in this system, p53 negatively regulates Nanog [65], suggesting a role for p53 in the control of both CSC selfrenewal and GBM growth.…”
Section: Opinionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this tumor type, Nanog, a homeoprotein required to maintain ES pluripotency [66], appears essential for SC functions as its inactivation reduces neurosphere formation in vitro and GBM growth in vivo. Importantly, in this system, p53 negatively regulates Nanog [65], suggesting a role for p53 in the control of both CSC selfrenewal and GBM growth.…”
Section: Opinionmentioning
confidence: 86%
“…This activity may contribute to the tumor suppressor function of p53 in brain CSCs, as recently shown in glioblastoma multiforme (GBM), a highly invasive type of brain tumor [65]. In this tumor type, Nanog, a homeoprotein required to maintain ES pluripotency [66], appears essential for SC functions as its inactivation reduces neurosphere formation in vitro and GBM growth in vivo.…”
Section: Opinionmentioning
confidence: 87%
“…Some embryonic stem cell markers associated with glioma identification and aggressiveness, such as Oct4, Nanog, and Sox2, have been used for the guidance of glioma therapeutic selection (Ben-Porath et al, 2008;Holmberg et al, 2011;Shats et al, 2011). Interestingly, Nanog expression correlates with the ability of GSC formation and the malignancy of glioma clinical samples (Zbinden et al, 2010;Niu et al, 2011).…”
Section: Molecular Markers Of Glioma Stem Cellsmentioning
confidence: 99%
“…In contrast, Ben-porath et al reported that gliomas express a core es-like stem signature including nAnog (26). subsequently, Zbinden et al addressed the function of nAnog in human glioblastomas and its relationship with HH-glI activity (27). However, comprehensive and systematic studies of nAnog mrnA and protein expression in glioma cell lines in vitro and in distinct multiple glioma pathological types particularly low-grade gliomas in vivo as well as its relationship with other important glioma undifferentiation markers in situ in cellular levels are still lacking mainly considering the scarce sample data or the limitations in methodology.…”
Section: Introductionmentioning
confidence: 99%